Investigating the dimensions of sustainability in the indigenous architecture of Hormozgan province - Naemeh Dabirinejad (مهندسی و مدیریت ساخت, 2021)
Sustainability as an important and necessary issue has attracted the attention of the international community in recent years, according to Derrida, sustainability is the last definitive solution in history. This research is based on the study and recognition of the principles of sustainable architecture and sustainable development, the study of sustainability patterns in the native architecture of Hormozgan province and the recognition of repetitive principles and values governing the architecture of native buildings in this province for sustainable development. To lead to an original architecture that sits on its proper climate bed away from the anonymity gaps of recent decades and is adapted to prevent damage to the environment. The present research has been done descriptively-analytically using valid library resources and field method. The results show that the native architecture of this region is completely in accordance with the principles of sustainable architecture and can be inspired by the formation of contemporary architecture.